Connotative Meaning In The Proverbs Of The Batak Angkola Language - Maharani; Andira, Ayu Andira; Hasibuan, Feni Jelita Hasibuan (Yayasan Kajian Riset dan Pengembangan RADISI, 2023)
This research was aimed to describe the connotative meaning in the proverbs of the Batak Language which used by people in Batak tribe which most live in North Sumatera. The writer formulates the problem of this research is how the connotative meaning in the proverbs of Batak language? The data of this research was the proverbs of Batak language which taken from Hatobangon who used proverbs in cultural ceremony in Tandihat Baru village region of Tapanuli selatan, North Sumatera. The method of this research was descriptive qualitative in order to analyze the semantic of connotative meaning of proverbs in Batak language. The results of this research showed that that the connotative meaning in the proverbs of Batak Language is having differences to denotative ones and its meaning depends on personal experience of Batak people experience and mostly relate the meaning of its proverbs to human life such as responsibility, hard work, social concern, and patience